The Effect of Listening to Pop Music on the Cognitive Performance of Students of the Faculty of Psychology UIN Raden Fatah Palembang - Ahmad Fikri Alfarizi; Rahmahdini, Dellbi; Jutia Asmarani; Rama Wulansari; Titin Juriani (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
Experimental research was conducted with the aim of knowing whether there was an effect of listening to pop music on the cognitive performance of psychology students at UIN (Islamic State University) Raden Fatah. In this experimental research, the method used is the quantitative method. The research design uses the Beetwee-subject design. The sample in this experimental research was 66 students from the psychology faculty of UIN (State Islamic University) Raden Fatah. The data collection technique for this study used a questionnaire where 33 students were given a questionnaire accompanied by the treatment of listening to pop songs while the other 33 students were not given the treatment of listening to pop songs. Data analysis of this experimental research used statistical methods which produced data with a mean in the group listening to music of 5. 64 with a standard deviation of 1.901 while in the group without listening to music with a mean of 5.15 a standard deviation of 2.002. From these results it can be concluded that there is a relationship between the effect of listening to pop music on the cognitive performance of psychology students at UIN (State Islamic University) Raden Fatah.